The Influence of Innovation Strategy on Improving Company Performance by PT. Kencana Energi Lestari, Tbk - Samperuru, Eston Septanugrah; Jusni, Jusni; Aswan, Andi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Innovation refers to the creation, development, and implementation of new ideas, processes, products, or services that result in significant improvement, progress, or change in a variety of fields. Innovation is a major driver of economic growth, community advancement, and competitive advantage for and organizations. This research is aimed at finding out the impact of process innovation and product innovation on the performance of the company by PT. Kencana Energy Lestari, Tbk. This research uses quantitative methods, while the collection of data is carried out in the form of a questionnaire that is shared to 25 respondents of the officials of PT. Kencana Energi Lestari, Tbk. The results of this research show that: (1) process innovations have a positive and significant impact on the performance of the company by PT. Kencana Energy Lestari, Tbk. (2) product innovations had a positive impact and significant effect on the company's performance by PT. Kencana Energi Lestari, Tbk.